THE REDISCOVERY OF MIRZO ULUGBEK’S IMAGE IN CONTEMPORARY LITERATURE - Ochilova Dilnoza Barnoyevna (The latest news and research in education, 2025)
This study examines the renewed interpretation of Mirzo Ulugbek’s image in contemporary literature, highlighting the transformation of his historical, scientific, and philosophical legacy in the modern cultural context. The analysis explores how post-Soviet national revival, expanded historical research, and global scholarly attention have contributed to a deeper understanding of Ulugbek as a multifaceted figure—an astronomer, mathematician, statesman, and humanist. Contemporary writers reinterpret his character with psychological nuance, philosophical depth, and a focus on intellectual freedom, emphasizing the enduring relevance of his scientific achievements, particularly the Zij-i Jadid-i Kuragoni. The study demonstrates that Ulugbek’s image has evolved from a tragic historical figure into a universal symbol of enlightenment, rational inquiry, and cultural identity.